Adaptation of the Pedestrian Walkways Design along the Trans Semarang Bus Corridor to COVID-19 (International Journal of Built Environment and Sustainability, 2022)
COVID-19 cases continue to increase in Indonesia, with an estimated value of 719,000 and an 8.37% mortality rate, due to the severity and potency of the deadly disease. One of the provinces that mostly contributes to the high mortality rate is Central Java, especially in populous areas like Semarang City. The spread of the virus occurs through direct contact between humans, forcing physical and social distances to become more important, especially in public spaces. Based on these conditions, city planning experts reportedly suggests a public space re-design process, adaptable to the current pandemic conditions, in order to provide a comfortable, safer, and sustainable urban life. Therefore, this study aims to analyze the integration of the mass transportation system (the Bus Trans Semarang) with the readjustment and redesign potentials of pedestrian walkways, in response to the COVID-19 pandemic. For the past two years, the development of pedestrian walkways has become an integral part of the Semarang City Government, in order to realize a sustainable transportation system. Furthermore, the pandemic has presently made pedestrian walkways less functional, due to public concerns on its spread in external areas. The retrieval spatial-based data of this study focused on the bus stops for the Trans Semarang Bus Corridor, which were potential points for the emergence of walking activities. The method used in the measurement of pedestrian activity included behavioral mapping and urban design analysis. This was to identify the pedestrian design indicators that were adaptive to the pandemic conditions. The simulation methods also assisted the data visualization process, by using spatial applications such as ArcGIS and Sketchup. After this, the calculation of the capacity was carried out, to determine the maximum limit of the available spaces. The results were in the form of indicators, such as additional width, lane division, as well as provision of health and hygiene facilities. These were the main recommendations applied on the pedestrian walkways' environmental characteristics, at various points in Semarang City.
Keywords: COVID-19 Pandemic, pedestrian walkways, Urban Design, Bus Trans Semarang